Intellectual Capital, Absorptive Capacity, and Innovation: A Dynamic Perspective in the Context of Industry 4.0 - Anthonius S. Hutabarat; Irawan R.D Budianto; Fajri Fajri (Jurnal Ekonomi, 2024)
The importance of intellectual capital (IC) and absorptive capacity (ACAP) in driving innovation in Industry 4.0 is emphasized in various studies. IC refers to intangible assets such as knowledge and expertise, while ACAP is a firm's ability to acquire and apply external knowledge. SMEs and technology transfer intermediaries can improve absorptive capacity through customized services. The dynamic perspective on IC and ACAP is crucial for innovation, with absorptive capacity being essential for leveraging intellectual capital. Innovation ecosystems allow SMEs to integrate resources and co-create Industry 4.0 solutions. The study highlights the need for effective measurement techniques to optimize the value of IC and the importance of creating awareness among investors and managers about its value.